Architecture and sequence stratigraphy of the Upper Coralline Limestone formation, Malta—Implications for Eastern Mediterranean restriction prior to the Messinian Salinity Crisis. (2nd March 2021) - Bialik, Or M.; Zammit, Raymond; Micallef, Aaron
Abstract: The Eastern and Western Mediterranean are separated by an elevated plateau that regulates water exchange between these two basins. The Maltese archipelago, situated atop this topographic high, offers a unique window into the evolution of this plateau in the lead up to the Messinian Salinity Crisis. The Upper Coralline Limestone Formation was deposited between the late Tortonian and the early Messinian and was probably terminated by palaeoceanographic events related to the Messinian Salinity Crisis. It represents the youngest Miocene sedimentary deposits outcropping in the Maltese archipelago. This shallow‐water carbonate unit can be used to trace palaeoenvironmental changes atop the sill between the Eastern and Western Mediterranean and to explain the possible water flow restrictions to the Eastern Mediterranean that could have preceded the Messinian Salinity Crisis. Here field surveys, and analysis of the depositional environment within the Upper Coralline Limestone in Malta, are combined with recently acquired multichannel seismic reflection profiles between Malta and Gozo, to reconstruct the depositional sequence in the Malta Plateau during the late Miocene. The Upper Coralline Limestone consists of multiple coralline and larger benthic foraminifera dominated facies, extending from subtidal to intertidal environments. These accumulated in two depositional cycles observed in both outcrop and seismic reflection data. Each cycle exhibits an early aggradation–progradation phase followed by a progradation phase and a final aggradation phase. These manifest themselves in the outcrops as shallowing and deepening upwards phases. These were deposited above a deep water unit and are indicative of a preceding uplift phase followed by filling of the accommodation space through the deposition of the Upper Coralline Limestone Formation in shallow marine depths. The presence of this highly elevated sill during the late Miocene could have restricted circulation to the eastern basin. Abstract : The Upper Coralline Limestone formation in Malta offers a unique look at the gateway between the West and East Mediterranean in the period before the Messinian Salinity Crisis (MSC). Here we revisit this unit using both field bases sedimentological analysis and seismic imaging to document the evolution of this sequence. The findings illustrate the ongoing uplift of the barrier between the basins before the MSC.